Stereoselective glucuronidation of formoterol by human liver microsomes - Zhang, Mei (Blackwell Science Inc, 2000)
AIMS: Formoterol is a β(2)-adrenoceptor agonist marketed as a racemic mixture of the active (R; R)- and inactive (S; S)-enantiomers (rac-formoterol). The drug produces prolonged bronchodilation by inhalation but there is significant interpatient variability in duration of effect. Previous work has shown that in humans formoterol is metabolized by conjugation with glucuronic acid but little is known about the stereoselectivity of this reaction. The aim of the present study was to investigate the glucuronidation of formoterol enantiomers in vitro by human liver microsomes. METHODS: The kinetics of formation of formoterol glucuronides during incubation of racemate and of single formoterol enantiomers with human liver microsomes (n = 9) was characterized by chiral h.p.l.c. assay. RESULTS: The kinetics of glucuronidation of the two formoterol enantiomers obeyed the Michaelis-Menten equation. Glucuronidation of formoterol was stereoselective and occurred more than two times faster for (S; S)-formoterol than for (R; R)-formoterol. In incubations with single formoterol enantiomers, the median (n = 9) K(m) values for (R; R)-glucuronide and (S; S)-glucuronide were 827.6 and 840.4 μm, respectively, and the median V(max) values were 2625 and 4304 pmol min(−1) mg(−1), respectively. Corresponding values determined in incubations with rac-formoterol were 357.2 and 312.1 μm and 1435 and 2086 pmol min(−1) mg(−1) for (R; R)- and (S; S)-glucuronide, respectively. Interindividual variation was large with the ratio of V(max)/K(m) (S; S/R; R) ranging from 0.57 to 6.90 for incubations with rac-formoterol. CONCLUSIONS: Our study demonstrates that glucuronidation of formoterol by human liver microsomes is stereoselective and subject to high interindividual variability. These findings suggest that clearance of formoterol in humans is subject to variable stereoselectivity which could explain the variation in duration of bronchodilation produced by inhaled formoterol in patients with asthma.